Strategi Pengembangan Usaha Mikro Kecil Menengah Jenang Kudus Di Kabupaten Kudus - Muhammad 'Irfan Murtadho; Endang Siti Rahayu; Mei Tri Sundari (Agricultural Socio-Economic Empowerment and Agribusiness Journal, 2024)
Kudus Regency is one of the districts in Central Java where the industrial sector is the primary sector that supports Gross Regional Domestic Income (GRDP). Small-scale producers of holy jenang have several problems that hinder business development. This research aims to identify the internal and external factors of Jenang Kudus micro, small, and medium enterprises (MSMEs) and determine alternative and priority development strategies. The basic method of this research is descriptive. Location determination was carried out purposively. The research key informants were six people to determine internal and external factors and 31 people to determine weights and ratings. The analysis uses the IFE EFE Matrix, IE Matrix, SWOT Matrix, and QSPM. There are 60 MSMEs in Jenang Kudus. The research results show that Jenang Kudus MSMEs can be maintained and maintained. Strategies that can be implemented include strengthening partnerships with distributors, maintaining brand image through improving product quality, diversifying flavor variants and packaging, and increasing product durability. Also, MSMEs can optimize online promotions, improve service quality to strengthen customer loyalty, and develop human resources through collaboration with the Kudus Regency Trade, Industry, and Cooperatives Service. The strategy that is the main priority is optimizing online promotions.